Stageless evaluation scheme for a vector Preisach model based on rotational operators - Nierla, Michael; Sutor, Alexander; Rupitsch, Stefan; Kaltenbacher, Manfred (Proceedings of the 17th International IGTE Symposium on Numerical Field Calculation in Electrical Engineering IGTE 2016, 2016)
Scalar Preisach models often exploit the so-called Everett function to determine the output of the hysteresis operator. Thereby, the switching state of the Preisach plane is not stored directly in form of discrete matrix entries. Instead, a list of dominant input maxima and minima is saved, which can be utilized to recreate the actual switching state. This allows a stageless, i.e. continuous, representation of the output. The extension of the scalar model towards a vector model using rotational operators prohibits the direct use of the Everett function as the switching state can no longer be reconstructed from a single list of maxima and minima. In our contribution, we present a stageless evaluation scheme for the vector Preisach model based on rotational operators that takes nested lists to exactly represent both the state of the rotational operator as well as the switching state.
Keywords: Everett Function; Hysteresis Modeling; Vector Preisach Model